2021
DOI: 10.3390/brainsci12010043
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Characterization of Posteromedial Hypothalamus in Anaesthetized Patients

Abstract: Deep brain stimulation (DBS) requires a precise localization, which is especially difficult at the hypothalamus, because it is usually performed in anesthetized patients. We aimed to characterize the neurophysiological properties posteromedial hypothalamus (PMH), identified by the best neurophysiological response to electrical stimulation. We obtained microelectrode recordings from four patients with intractable aggressivity operated under general anesthesia. We pooled data from 1.5 mm at PMH, 1.5 mm upper (uP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…Recently, it has been shown that the types of mAPs in the hypothalamus are similar to those described in the thalamus [19,20], with the majority of cells showing three phases. Despite the similar morphology in both brain structures, the properties of the mAPs were different, showing that mAP morphology is region specific.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Recently, it has been shown that the types of mAPs in the hypothalamus are similar to those described in the thalamus [19,20], with the majority of cells showing three phases. Despite the similar morphology in both brain structures, the properties of the mAPs were different, showing that mAP morphology is region specific.…”
Section: Discussionmentioning
confidence: 69%
“…Despite the similar morphology in both brain structures, the properties of the mAPs were different, showing that mAP morphology is region specific. However, in the thalamus, we did not record the amAPs that were recorded in the hypothalamus [20]. This fact adds another element of regional specificity regarding the structure of action potentials.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations